Successful cryopreservation of marine invertebrates immune cells enables long-term studies of common octopus, Octopus vulgaris Cuvier 1797, hemocyte immune functions - Costa, María M.; Paredes, Estefania; Peleteiro, Mercedes; Sánchez-Ruiloba, Lucía; Gambón, Francisco; Dios, Sonia; Gestal, Camino (Frontiers in Immunology, 2025)
The common octopus, Octopus vulgaris Cuvier 1797, as all cephalopods, presents highly evolved characteristics compared to other classes of molluscs and the whole invertebrate phyla. However, to date, there is not much information about its immune system, and studying the defense mechanisms is a key step in understanding their response to external aggressions, having the tools to anticipate animal health problems and ensure their welfare. The lack of cell cultures in molluscs is a major problem when carrying out in vitro assays that help to deepen our knowledge of this species’ main immune cells. Cryopreservation becomes an alternative to maintaining viable and functional cells after freezing/thawing processes. Having access to good high-quality cells for long periods allows cover a wider repertoire of studies, time courses, and the avoidance of logistical issues such as loss of viability and/or functionality, time constraints, or sample transport challenges. Additionally, high-quality cell suspensions are essential for successful applications, such as single-cell sequencing, where viability and functionality are the key to optimal identification. The optimal medium, cryoprotective agent, and freezing/thawing protocol for octopus hemocytes have been selected. We show here the first functional results from cryopreserved hemocytes. Cells cryopreserved in MAS medium supplemented with EG maintained viability above 80% after 15 weeks post cryopreservation storage at -80°C, and their functional ability to phagocytize bacteria similar to fresh cells. Moreover, thawed acclimated cells exhibited a gene expression pattern comparable to fresh cells, as opposed to directly thawed cells. The acclimation process after thawing was essential to recover the functional activity of the cells and to return to levels of gene expression involved in oxidative stress similar to fresh cells.The results presented here will facilitate functional studies of octopus immune cells and provide tools for cell preservation in other molluscs species.